Makna dan Sejarah Ajaran Zuhud dalam Tasawuf - Eliza Eliza (Universitas Islam Negeri Imam Bonjol Padang, 2013)
When observed between the teachings of Sufism, there is an illustrated motivation to be anti-life and anti-social world. Zuhud is seen as a state of the world and leave material life. In an effort to get closer to God, a Sufi must turn away and leave something to be cherished any material or worldly pleasures with hope and want something better shape and be spiritual or happiness hereafter.